The use of logistic regression in the ovarian cancer diagnostics - Sompolska-Rzechuła, Agnieszka; Machowska-Szewczyk, Małgorzata; Chudecka-Głaz, Anita; Cymbaluk-Płoska, Aneta; Menkiszak, Janusz (Wykorzystanie regresji logistycznej w diagnostyce raka jajnika, 2014)
In the present elaboration an attempt has been made to build the logit model which makes it possible to specify the probability of diagnosing the ovarian carcinoma in the female patients with pathological lesion in the ovary. Based on sampling of 210 patients treated and diagnosed at the Teaching Hospital of Operative Gynaecology and Gynaecological Oncology of Women and Girls of the Pomeranian Medical University, the evaluations of the parameters of two logit models were determined and the estimation of the quality of obtained models was made. The obtained results may contribute to supporting of the ovarian cancer diagnostics.
Ekonometria = Econometrics, 2014, Nr 3 (45), s. 151-164
Keywords: logit model; classification quality of female patients; ovarian cancer; model logitowy; jakość klasyfikacji pacjentek; rak jajnika